Hosoya and Harary Polynomials of TOX(n),RTOX(n),TSL(n) and RTSL(n) - Lian Chen; Abid Mehboob; Haseeb Ahmad; Waqas Nazeer; Muhammad Hussain; M. Reza Farahani (Discrete Dynamics in Nature and Society)
In the fields of chemical graph theory, topological index is a type of a molecular descriptor that is calculated based on the graph of a chemical compound. In 1947, Wiener introduced “path number” which is now known as Wiener index and is the oldest topological index related to molecular branching. Hosoya polynomial plays a vital role in determining Wiener index. In this report, we computed the Hosoya and the Harary polynomials for TOX(n),RTOX(n),TSL(n), and RTSL(n) networks. Moreover, we computed serval distance based topological indices, for example, Wiener index, Harary index, and multiplicative version of wiener index.